FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA PADA MAHASISWA STIE PANCASETIA BANJARMASIN - Firda Nosita (Jurnal Ilmu Ekonomi dan Bisnis, 2019)
Unemployment is a classic problem in many countries. Entrepreneurship is one of way to reduce unemployment. But, not at all the people who interested in entrepreneurship. The purpose of the study is to determine whether a person’s internal and external factors influence entrepreneurial interest. The study was conducted on students of the STIE Pancasetia Banjarmasin. The sample in this study were 230 active students of STIE Pancasetia Banjarmasin. The data was collected by distributing questionnaires online. The results showed that the innovation, profit expectations and the environment had a significant effect on the entrepreneurial interest and the dominant variable is innovation. Entrepreneurship requires a person to be more observant in capturing opportunities amid tight competition. Innovation is one of the important factor for someone to at least enter, survive and compete. Entrepreneurship allows flexibility in determining time, operational and return. Entrepreneurship interest should be developed in order to resolve the unemployment and employment creation.